Improving the skills of IKBI Women's Group Helvetia Plantation PTPN II through hydroponic vegetable food diversification training - Sinamo, Karina Nola (Talenta Publisher Universitas Sumatera Utara, 2025)
The service partner is a group of women in Ikatan Keluarga Besar Istri (IKBI) PTPN II Helvetia Plantation. Partner has previously succeeded in cultivating vegetables hydroponically, starting from the seeding stage to harvesting in the greenhouse of the Helvetia Plantation. However, the harvested vegetables have not yet undergone further processing. Therefore, this community service aimed to provide education and training on processing hydroponic vegetables into other food products. The method of community service activity was the practice of food processing from hydroponic vegetables by actively involving partner. The service team conducted training on the diversification of hydroponic vegetable food products into spinach chips, water spinach stick crackers, and bok choy’s small martabak. The service team also provided training on packaging and labeling of food products produced to improve the appearance of the products so that they look more attractive, maintaining product safety from contamination, and providing product information. The results obtained after the training activity from 20 participants were that 85% (17 participants) understood how to make these food products and 75% (15 participants) were interested in practicing it independently at home. The partner also carried out an organoleptic test of the three food products as panelists and found that the partner liked the color, aroma, taste, and texture of the food products.